E-018 Treatment of Ruptured Blood-blister-like Aneurysms in the Subacute Phase: Clinical and Angiographic Outcome. (29th July 2016) - Di Maria, F; Gabrieli, J; Bartolini, B; Pistocchi, S; Chiras, J; Sourour, N; Clarençon, F
Abstract : Purpose: Ruptured Blood blisterlike (BBL) aneurysms represent a therapeutic challenge. Timing of treatment and technique of choice are still a subject of debate. We report our experience in the endovascular treatment of such lesions in the subacute phase. Methods: Between June 2011 and January 2015, 6 ruptured BBL aneurysms were treated at our institution. Four were located in the carotid siphon, 2 in the posterior circulation. Endovascular procedures were carried out between day 7 and day 15 after the hemorrhagic event. One patient was treated surgically. Flow-diverter stents (FDS) were used in 4 cases. Two telescopic laser-cut stents were used in one case. Double antiplatelet therapy was started 4 days before treatment in 1 case and the day of the procedure in the remaining 4 cases. Angiographic follow-up was carried out by MRA and DSA at 1 month, 6 months and 1 year. Results: All endovascular procedures were performed without technical difficulties. Antiplatelet treatment was started 4 days prior to procedure in one case and the day of the intervention in the other cases. One patient presented a transient motor deficit at day 1 after treatment. One patient had a peroperative cerebellar ischemia after FDS deployment, despite antiplatelet treatment. One patient treated by surgery had a fatal brain ischemia after peroperative aneurysmal rupture that eventually required clipping of the carotid siphon. Imaging follow was available for the remaining 5 patients. No patent rebled prior to treatment or during follow-up. Three out of five aneurysms were completely occluded at latest follow-up. Conclusion: Modern endovascular techniques for the treatment of ruptures BBL aneurysms, including the use of flow-diversion, seem promising. Treatment in the subacute phase may be considered as an option in relation to other clinical issues (patient WFNS grade, risk of rebleed under antiplatelet therapy, ventricular shunting) when pondering overall risks and benefits in patient management. Disclosures: F. Di Maria: None. J. Gabrieli: None. B. Bartolini: None. S. Pistocchi: None. J. Chiras: None. N. Sourour: None. F. Clarençon: None.